Semen Quality of Garut Rams feed by Different Protein Sources and Their Implementation Potential in Small Farms of West Java - Kurnia Bagus Ariyanto; Lilis Khotijah; Dewi Apri Astuti; Raden Iis Arifiantini; Jean-Baptise Menassol (Agricultural Faculty, 2020)
ABSTRACT. Maggot Hermetia illucens (Maggot Black Soldier Fly, MBSF) is an alternative protein source besides soybean meal (SBM) which may be used as a feed for improving the quality of semen particularly in Garut rams to support prolific nature. The aims of this study were to analyzed and compare the impact of different protein sources in feed on semen quality of Garut rams, and to assess the prediction ability of Garut rams to serve ewe in small-scale breeders in West Java, Indonesia. This study was conducted using a completely randomized design with 3 treatments and 4 replications, consisted of Brachiaria humidicola (BH) grass and T1 (concentrate contains 20% of SBM), T2 (concentrate contains 10% of SBM and 10% of MBSF), and T3 (concentrate contains 20% of MBSF). The parameters measured were feed consumption, semen quality (macroscopic and microscopic characteristics), also a potential ability of rams to serve ewe. The results showed there were no significant effect on protein consumption, semen volume, semen pH, semen color and consistency, sperm mass movement, sperm motility, sperm concentration, sperm morphology, and prediction potential ability to serve ewe. However, the result showed a significant effect (P0.05) on sperm viability and sperm plasma membrane integrity. Sperm plasma membrane integrity of ram feed with T3 was better than T1 and T2 (P0.05). The prediction potential ability rams to serve ewes on MBSF treatment was 38 heads, while in T1 and T2 were 43 and 57 heads, respectively. In conclusion, MBSF can be an alternative source of protein besides SBM to improve the semen quality of Garut rams.ABSTRAK. Maggot Hermetia illucens (Maggot Black Soldier Fly; MBSF) adalah sumber protein alternatif selain bungkil kedelai (SBM) yang dapat dipergunakan sebagai pakan untuk memperbaiki kualitas semen terutama pada domba Garut untuk mendukung sifat prolifik. Tujuan penelitian ini adalah menganalisis dan membandingkan dampak pemberian sumber protein berbeda terhadap kualitas semen domba Garut dan untuk menilai kemampuan domba Garut pejantan dalam melayani betina pada peternakan rakyat di Jawa Barat, Indonesia. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 3 perlakuan dan 4 ulangan yang terdiri dari rumput Brachiaria humidicola (BH) dan T1 (konsentrat mengandung 20% SBM), T2 (konsentrat mengandung 10% SBM dan 10% MBSF), dan T3 (konsentrat mengandung 20% MBSF). Parameter yang diukur adalah konsumsi pakan, karakteristik semen (makroskopis dan mikroskopis) serta potensi domba jantan melayani betina. Hasil Penelitian menunjukkan tidak ada perbedaan signifikan pada konsumsi protein pakan, volume semen, pH semen, warna dan konsistensi semen, gerakan massa sperma, motilitas sperma, konsentrasi sperma, morfologi sperma, dan prediksi potensi pejantan dalam melayani betina. Namun, hasil penelitian menunjukkan terdapat perbedaan (P0.05) pada viabilitas sperma dan membran plasma utuh sperma. Membran plasma utuh pada perlakuan T3 lebih baik dibandingkan perlakuan T1 dan T2 (P0.05). Prediksi potensi betina terlayani dari pejantan yang diberi pakan MBSF adalah 38 ekor, sedangkan yang diberi SBM dan kombinasinya adalah 43 dan 57 ekor. Kesimpulan penelitian ini adalah MBSF dapat menjadi alternatif sumber protein selain bungkil kedelai dalam memperbaiki kualitas sperma domba Garut.